Respiratory events and periodic breathing in cyclists sleeping at 2,650-m simulated altitude - Kinsman, T. A.; Hahn, A. G.; Gore, C. J.; Wilsmore, B. R.; Martin, D. T.; Chow, C. M. (Journal of Applied Physiology, 2002)
We examined the initial effect of sleeping at a simulated moderate altitude of 2,650 m on the frequency of apneas and hypopneas, as well as on the heart rate and blood oxygen saturation from pulse oximetry (SpO2) during rapid eye movement (REM) and non-rapid eye movement (NREM) sleep of 17 trained cyclists. Pulse oximetry revealed that sleeping at simulated altitude significantly increased heart rate (3 ± 1 beats/min; means ± SE) and decreased SpO2 (6 ± 1%) compared with baseline data collected near sea level. In response to simulated altitude, 15 of the 17 subjects increased the combined frequency of apneas plus hypopneas from baseline levels. On exposure to simulated altitude, the increase in apnea was significant from baseline for both sleep states (2.0 ± 1.3 events/h for REM, 9.9 ± 6.2 events/h for NREM), but the difference between the two states was not significantly different. Hypopnea frequency was significantly elevated from baseline to simulated altitude exposure in both sleep states, and under hypoxic conditions it was greater in REM than in NREM sleep (7.9 ± 1.8 vs. 4.2 ± 1.3 events/h, respectively). Periodic breathing episodes during sleep were identified in four subjects, making this the first study to show periodic breathing in healthy adults at a level of hypoxia equivalent to 2,650-m altitude. These results indicate that simulated moderate hypoxia of a level typically chosen by coaches and elite athletes for simulated altitude programs can cause substantial respiratory events during sleep.